Investigations of the EPR parameters for the tetrahedral [FeX₄]- clusters in AgX (X=Cl, Br) - Song, B.-T.; Wu, S.-Y.; Kuang, M.-Q.; Zhang, Z.-H. (Condensed Matter Physics, 2012)
The EPR parameters g factors and the superhyperfine parameters for the tetrahedral [FeX₄]- clusters in AgX (X=Cl, Br) are theoretically investigated from the perturbation formulas of these parameters for a 3d⁵ ion under tetrahedra by considering both the crystal-field and charge transfer contributions.The related model parameters are quantitatively determined from the cluster approach in a uniform way. The g-shift Δg (=g-gs, where gs≈2.0023 is the spin only value) from the charge transfer contribution is opposite (positive) in sign and much larger in magnitude as compared with that from the crystal-field one. The importance of the charge transfer contribution increases rapidly with increasing the covalency and the spin-orbit coupling coefficient of the ligand and thus exhibits the order of AgCl<AgBr. The unpaired spin densities of the halogen ns, npσ and npπ orbitals are quantitatively determined from the related molecular orbital coefficients based on the cluster approach. Параметри g факторiв електронного парамагнiтного резонансу i супертонкi параметри для тетраедральних кластерiв [FeX₄]− у AgX (X = Cl, Br) дослiджуються теоретично, використовуючи теорiю збурень для цих параметрiв для 3d⁵ iона в тетраедрi з врахуванням вкладiв вiд кристалiчного поля i перенесення заряду. Параметри моделi кiлькiсно визначаються з кластерного пiдходу в єдиний спосiб. Вклад у g-зсув 4g (= g −gs , де gs ≈ 2.0023 — значення спiну), отриманий iз врахування зарядового перенесення є протилежний (позитивний) за знаком i набагато бiльший за величиною в порiвняннi з вкладом, отриманим вiд врахування кристалiчного поля. Важливiсть врахування зарядового перенесення зростає з ростом ко-валентностi i коефiцiєнту спiн-орбiтальної взаємодiї лiганди i отже демонструє, що AgCl < AgBr. Густини неспарених спiнiв галогенiв, npσ i npπ орбiталей кiлькiсно визначаються з молекулярних орбiтальних коефiцiєнтiв, що базуються на кластерному пiдходi.